Mises en discours de l’expérience visuelle et cognition située : couleurs et espace. - Danièle Dubois; Caroline Cance (Corela)
Our contribution is concerned with the relationships between language and cognition as discussed since 1991 (see Vandeloise, 1991) focusing on lexicalisation and categorisation of colours and their contribution to the construction of space. Following Rosch’s insights of an experiential and embodied cognition, we develop a broader conception of a situated cognitive approach of lexical meaning. Cognitive representations are considered as resulting from complex processes constructed from perceptual experience, lexical resources and discourse processing. Empirical results concerned with lexical resources available within French language and involved in different practices of colours allow to identify different cognitive representations of colours : as subjective effects, as matter, as sources, as entities of the physical world (Dubois & Grinevald, 2003). Our analyses further explore the constraints on conceptual elaborations of colours through the syntactic inscription of colour words in discourses allowing the identification of objects and the referenciation to space (Cance, 2008). Our conclusion emphasises on the requirements for a diversity of experimental protocols and analyses to produce non restrictive data in order to adequately account for the diversity of colour conceptualisations and for their role in the referenciation processes to objects and space.